A Phenotypical and Physiological Characterization of Some Genotypes of Prunus Cerasia Spreading in Lattakia - Ismael, Haitham; Mahfod, Hafez; Nizam, Mohammad (Latakia University Journal -Biological Sciences Series, 2013)
This study was carried out on the wild prevailing Prunus cerasia in the Scientific Agricultural Research Center in Lattakia during 2012 – 2013. The traits of 20 phenotypes and the germination of 12 phenotypes were studied at the study sites (Ein Al-Baydha, Kersana, Qastal Al- Mua’af, Kassab). The results showed a difference in some phenotypical traits. The cluster analysis showed five separate phenotypes. The best germination rate was at 10◦C, however, phenotypes (A9 – A10) prevailing in Kassab Area showed the best percentage and velocity of germination. Results also showed that while light has a positive effect on seed germination, the applied stratification method has no effect of stratification method on the studied phenotypes.